(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2022)
Antoni Muntadas, by creating art, explores the individual and our society, particularly the role of technology to mediate and create reality. The paper analyses the design strategies of two of his works: The Board Room and The File Room, with particular attention to the integration of the virtual in the art installation. The two cases allow us to see two possibilities of interaction between the public and the multimedia artistic project.